“Loving thy neighbour” in times of violence: Social cohesion and collective efficacy in South Africa - Barolsky, Vanessa (PINS-Psychology in Society, 2024)
This article engages with the problematic of violence and its relationship to conditions of solidarity at a local level in the newly democratised nation-state of South Africa. It explores this question through the concept of social cohesion, which has become a significant part of South African discourse over the past decade and has been the object of policy concern in the global north since the 1990s. More recently the concept of social cohesion has been linked to the question of violence through the theory of collective efficacy, which sees social cohesion enacted in support of the “common good” as functioning as a critical “protective” factor against violence. The paper interrogates these international and local discourses around social cohesion and its relation to violence through an ethnographic examination of the empirical conditions of solidarity and violence in one township, Khayelitsha, in the Western Cape, South Africa. The article reveals the dissonances between the material conditions in Khayelitsha, international discourses on social cohesion and the South African state’s aspirations towards new forms of civic solidarity founded on a Constitutionally defined “common good”. Instead collective, informal, and sometimes violent forms of social order based on communitarian values and practices, displace or contest the state’s law and shape forms of sociality that offer both extraordinary support and the possibility of spectacular violation.